The detrital zircon record of Variscan to post‑Variscan tectonosedimentary and magmatic processes in the Tauern Window (Eastern Alps) - Veselá, P. (2022)
Coupled U–Pb and Lu–Hf LA-ICP-MS detrital and igneous zircon data were obtained from metasedimentary sequences (Kaserer Formation, Schmirntal Quartzite, Seidlwinkel Formation, Bündnerschiefer Basin, Riffler Basin) of the western Tauern Window (Eastern Alps). Results show maximum deposition ages between the Late Permian and the Triassic, indicating protracted sedimentation and magmatism between the Late Paleozoic and the Mesozoic. The Lu–Hf fingerprint shows a change from subchondritic to variable subchondritic to suprachondritic compositions at ca. 290 Ma, possibly documenting the transition from Late Paleozoic Variscan post-collisional processes to intracontinental extension. Lithospheric thinning and magmatic underplating may explain the observed Hf isotopic evolution as the result of mixing of crustal and mantellic sources. From a paleogeographical perspective, results confirm that the Tauern Window was situated between Alpine basement units (South Alpine, Austroalpine and External Massifs) and the Bohemian Massif during the Permian–Triassic.